Quantitative approach to the ethnomedicinal study of the ethnic communities of Rangia subdivision, Assam, North East India - Baruah, Sanjib; Basumatary, Dhriti; Brahma, Priyanka (Ethnobotany Research and Applications, 2024)
Background: In developing nations, using plants and plant resources for various ethnobotanical purposes is a prevalent practice. Assam is part of the Indo-Myanmar biodiversity hot spot, one of the 25 mega-diverse regions on planet Earth. Assam is unparalleled, as nature has been uniquely generous in endowing it with varied ethnic groups. This study conducted an ethnobotanical survey of plant diversity at Rangia subdivision of Kamrup District, Assam, India. Methods: Ethnomedicinal information was gathered through carefully planned questionaries and interviews with 43 informants across 11 villages in the Rangia subdivision of Assam. The data was analyzed using various quantitative indices like Use value (UV), Informant Consensus Factor (ICF), and Family Importance Value (FIV). Results: In the present findings, 60 plant species belonging to 42 families, and 87 genera used by the ethnic people in the study areas have been documented. A total of 43 key informants were interrogated comprising men and women. A quantitative ethnobotany index analysis helps us to identify the utility of various significant species to treat some of the common ailments that are claimed by traditional medicine practitioners Conclusions: It is important and pertinent for society to look into the traditional knowledge of ethnic groups employing different plants to treat illnesses. In addition to providing important avenues for the promotion of traditional herbal therapeutic practices, more research into the ethnobotanical aspects of the region will also provide scientific validation. Moreover, species with strong UVs could offer helpful leads for pharmacological study in the future. Keywords: Quantitative ethnobotany, medicinal plants, Use value, traditional knowledge